The effectiveness of semantic web based preschool cognitive skills tutoring system: An empirical study - Abbas, M.A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Two groups had participated in a study on the effectiveness of Semantic Web based mobile application for preschool cognitive skills learning. The first group had the traditional method with textbooks and teacher's teaching. The second group worked with the proposed application at school along with the classroom sessions. A quasi experimental pre and post tests model was conducted to measure the learning gain for classification and relatedness cognitive skills. The results had shown significant gain by the second group over the first one and hence support the use of the proposed application in practice. The conclusion is that proposed application can be used as teaching support along with formal school learning. Â© 2015 IEEE.